1979
DOI: 10.1139/b79-155
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of sporulation in the Hemiascomycetes Ascoidea corymbosa, A. rubescens, Cephaloascus fragrans, and Saccharomycopsis capsularis

Abstract: Sporulation in four species belonging to three different families of the Hemiascomycetes is described from serial sections. The results show that in each species the formation of the ascospore wall is initiated at a specialized spindle pole body. Spore delimitation proceeds concurrently with the last nuclear division in the ascus. The findings support the taxonomic position that these species belong to a group that includes the yeasts but that is distinct from the Euascomycetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1980
1980
1992
1992

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…It occurs in the Hemiascomycetes (Curry, 1985: 401 ). This type of ascosporogenesis is reported for Dipodascopsis tothii (Curry, 1985: 410) and all other members of the Hemiascomycetes (Ashton andMoens, 1979: 1280), e.g. species of Saccharomyces, Ascoidea, Cephaloascus, and Saccharomycopsis (Ashton andMoens, 1979: 1259).…”
Section: Spores and Gametessupporting
confidence: 60%
See 2 more Smart Citations
“…It occurs in the Hemiascomycetes (Curry, 1985: 401 ). This type of ascosporogenesis is reported for Dipodascopsis tothii (Curry, 1985: 410) and all other members of the Hemiascomycetes (Ashton andMoens, 1979: 1280), e.g. species of Saccharomyces, Ascoidea, Cephaloascus, and Saccharomycopsis (Ashton andMoens, 1979: 1259).…”
Section: Spores and Gametessupporting
confidence: 60%
“…The two species Saccharomycopsis capsularis and Ascoidea corymbosa have uninuclear cells (Ashton and Moens, 1979) but it is not clear whether septal pores are present or not. 7.…”
Section: Class Protobasidiomycetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Beckett (4) argued that the terms prospore wall (3,42) and spore wall primordium (60) suggested that spore wall material was laid down between the double membranes before nuclear delimitation was completed; however, this sequence of events has not been shown to occur. He proposed the term spore-delimiting membrane (SDM) as an alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Beckett (4) summarized the postulated origins, which included in Hemiascomycetes de novo synthesis in association with the NAO (3,6,25,42,43,59) as well as alternative modes (16,35,48,58), many of which could be interpreted as de novo synthesis or had inconclusive data. Taphrina deformans (51,52) was the only exception with the ascus plasma membrane as its apparent origin.…”
Section: Discussionmentioning
confidence: 99%